Empirical analysis of Chinese overseas power plant investments: Likelihood of suspensions and associated environmental risks - Yangsiyu Lu; Xiao Yan Zhou; B. Alexander Simmons (iScience, 2023)
Summary: Power sector investment is crucial to accelerate a sustainable energy transition, but not all investments are successful. We examine 1,393 Chinese overseas electric power projects across 78 countries over the past two decades. We identify 5% that have been canceled or delayed, with coal and hydro projects having much higher suspension rates than solar and wind projects. We find electric projects with higher environmental risks are more likely to be suspended. Specifically, coal projects located in more densely populated areas where more people are exposed to air pollutants, in countries with more fatalities from extreme weather events, and in places with a record of environmental protests, are more likely to be suspended. Additionally, hydro projects closer to protected areas have a higher suspension rate. Our results suggest that refraining from investing in environmentally risky projects helps mitigate environmental damages and prevents financial losses due to cancellation and postponement.